The effects of ACSM-based exercise on breast cancer-related lymphoedema: a systematic review and meta-analysis - Luan, Biqing; Li, Zhiqiang; Yang, Qizhi; Xu, Zhihui; Chen, Yaqin; Wang, Meiting; Chen, Wenlin; Ge, Fei (Frontiers in Physiology, 2024)
Background: Breast cancer-related lymphedema (BCRL) frequently occurs after axillary lymph node dissection and remains incurable even with lymphaticovenular anastomosis. Exercise interventions have emerged as a potential non-pharmacological management approach. However, standardized exercise recommendations tailored to BCRL patients are lacking. Purpose: This study evaluated the impact of high and low compliance exercise interventions, aligned with ACSM recommendations, on QOL, ROM, and arm volume in BCRL patients. It further aimed to determine the optimal exercise dosage, assessed via the FITT (frequency, intensity, time, type) principle, that maximizes health benefits for BCRL patients. Methods: Adhering to the PRISMA guidelines for systematic reviews and metaanalyses, we conducted a comprehensive literature search in various databases, including PubMed, Embase, Cochrane Library, and Web of Science, encompassing the period from the inception of these databases to December 2023. We extracted data on exercise form, frequency, intensity, duration, repetitions, and sets from the identified studies. Subsequently, a meta-analysis and review were conducted. The exercise interventions were evaluated based on ACSM recommendations and categorized as either high or low compliance with ACSM standards. Fixed or random effects models were employed to compare outcomes across study subgroups with comparable results.Additionally, funnel plot analyses, sensitivity analyses, and Egger's and Begg's tests were conducted to evaluate the potential for bias.Results: 15 studies encompassing 863 patients with BCRL were analyzed. Eleven studies exhibited high ACSM compliance, while four demonstrated low ACSM compliance. Regarding QOL, the overall SMD was 0.13 (95% CI: -1.07, 1.33). Specifically, the SMD for the high-adherence subgroup was 0.91 (95% CI: 0.33, 1.49; p = 0.002). For ROM, the overall SMD was 1.21 (95% CI: -0.19, 2.61). For arm volume, the overall SMD was -0.06 (95% CI: -0.22, 0.10). QOL results differed significantly in the high-adherence subgroup, whereas no significant effect on ROM or arm volume was observed.The study revealed significant QOL improvements in patients with high ACSM compliance, contrasted with those with low compliance. Conversely, no notable changes in ROM or arm volume were observed. Notably, the high adherence group tended to show better ROM during exercise and stable arm volume. Future research is needed to validate these findings.